Chromosomal aberrations in couples with pregnancy loss: A retrospective study - Asoke K Pal; Prafulla S Ambulkar; Jwalant E Waghmare; Vandana Wankhede; Moreshwar R Shende; Aaditya M Tarnekar (Wolters Kluwer Medknow Publications, 2018)
Background: Recurrent pregnancy loss is a challenging reproductive problem, and chromosomal anomalies approximately affect 2%-8% of couples with recurrent pregnancy loss. The chromosomal abnormality, especially balanced translocation rearrangement in either parent, is the important cause of recurrent spontaneous abortion. Aims: The aim of this study was to investigate the role and prevalence of chromosomal anomalies in recurrent miscarriages. The results will be helpful for counseling and make the decision for alternative options and precaution for the affected couples and also support to make a national database. Settings and Design: The present retrospective study was carried out in 172 couples (344 individuals) having the history of three or more recurrent spontaneous abortion. The cytogenetic analysis was done in all 344 individuals using G-banding and karyotyping. Results: Out of 172 couples, 17 couples (9.88%) had different types of structural or numerical chromosomal abnormalities. The structural aberrations were observed in 15 (8.72%) couples, and numerical aberrations were seen in 2 (1.16%) couples. Out of 17 couples, 8 (47.05%) had balanced translocations, 2 (11.76%) had the Robertsonian translocation, 5 (29.41%) had the pericentric inversion of chromosome 8, 9, and Y, and only 2 (11.76%) women showed sex chromosome numerical aberrations. Conclusions: Cytogenetic analysis should be an important routine investigation in couples with repeated miscarriages. Cytogenetic analysis is essential and helpful for genetic counseling to take precaution and implementing proper reproductive alternatives. Studies on the genetic basis of pregnancy loss should be taken up to generate data on these issues from different regions.